Earning while learning: how students are thriving in the gig economy - Muda, Salwa; Musman, Musliha (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s digital era, university students are increasingly balancing academic responsibilities with financial pressures due to rising living costs and the desire for independence. The growth of the gig economy characterised by flexible, short-term work enabled by digital platforms has transformed how students earn income. From food delivery and content creation to freelancing and online tutoring, gig work offers accessible opportunities beyond traditional 9-to-5 jobs, becoming not only a source of extra income but also a pathway for career development and financial stability.